VIDEO PROJECT ACTIVITY AND FRESHMEN'S LEARNING AUTONOMY IN INTERMEDIATE SPEAKING COURSE - Raharjo, Yohanes Maria Restu Dian; Hasibuan, Anastasia Ronauli; Natasha, Kayla (Universitas PGRI Sumatera Barat, 2024)
The availability of technological learning media offers easiness in determining relevant learning activities. Moreover, this can also be integrated into the principle of a student-centered learning system which would promote students to be more independent in managing their study. This study investigated the relationship between the video project activity and freshmen’s learning autonomy in the Intermediate Speaking course. Nine students of the English Language Education Study Program of the 2022/2023 batch were involved as the participants of this correlational study. To gather the data, a learner autonomy questionnaire and the result of students’ speaking video project were used. The Pearson Product Moment formula was used to analyze the correlation of the two variables. The findings of this study confirmed possible implications between the correlational of “learning autonomy” and “learning achievement”.